IDENTIFIKASI PENGETAHUAN DAN SIKAP REMAJA TENTANG INFEKSI MENULAR SEKSUAL - Nurul Khoirun Nisa; Sunarti Sunarti (Jurnal EDUNursing, 2023)
Sexually Transmitted Infections are still increasing and are one of the main causes of the poor health of a country and the world. The purpose of the research was to identify the knowledge and attitudes of adolescents about sexually transmitted infections in STIKes Kapuas Raya, Sintang District. This study used a cross sectional design, as many as 62 samples with simple random sampling. Data analysis using Chi-Square Test. Respondents with good knowledge about Sexually Transmitted Infections are mostly good, namely 74%. Respondents with poor knowledge of Sexually Transmitted Infections, namely 26%. Respondents with a positive attitude 87%. Respondents with a negative attitude that is equal to 13%. Student knowledge about Sexually Transmitted Infections is not affected by the age of the respondent, but in the aspect of Student Attitudes about Sexually Transmitted Infections it is influenced by age and gender. Keywords: Education, knowledge, attitudes, Sexually Transmitted Infections